Analysis of Pathogenic Bacteria in Oysters (Crassostrea cucullata) - Ruslan Hasani; Zakaria; Hamsina; Erni Indrawati; Ifa Safira (Jurnal Penelitian Pendidikan IPA, 2023)
The research objective was to analyze the pathogenic bacteria in oysters (Crassostrea cucullata). This research was conducted at the Makassar Laboratory (BBLK). The samples used were oyster meat and innards. Parameters observed were Escherichia coli and Salmonella sp. Research on samples was carried out using biochemical tests to identify the type of bacteria in the sample by planting the bacteria on Nutrient Agar (NA) media. The results showed that oyster meat in Lengkese Village, Takalar Regency was negative for E. coli and Salmonella sp. While the oyster meat samples in Coppo Village, Barru Regency showed positive E. coli bacteria and negative Salmonella sp.